Diversification and top management team complementarity: is performance improved by merging similar or dissimilar teams? - Krishnan, Hema A.; MILLER, ALEX; Judge, William Q. (Strategic Management Journal, 1997)
This study examines the impact of complementary top management teams (defined as differences in functional backgrounds between the acquiring and acquired firm managers) on post-acquisition performance. Based on a sample of 147 acquisitions completed during 1986–88, we find that complementary backgrounds have a positive impact on postacquisition performance in both related and unrelated acquisitions. Another major finding is that complementarity is negatively related to top management team turnover among acquired managers, suggesting that differences in functional backgrounds are more easily integrated into the new organization. Finally, top management team turnover among acquired managers is negatively related to postacquisition performance. These findings highlight the importance of examining complementarity in terms of differences, and reinforce the notion that differences have the potential to create unique value for the organization. © 1997 by John Wiley & Sons, Ltd.